2002
DOI: 10.1161/01.cir.0000039341.57809.1e
|View full text |Cite|
|
Sign up to set email alerts
|

NCX-4016 (NO-Aspirin) Inhibits Lipopolysaccharide-Induced Tissue Factor Expression In Vivo

Abstract: Background-NCX-4016 is an acetylsalicylic acid (ASA) derivative containing a nitric oxide-releasing moiety. Compared with ASA, NCX-4016 has a broader spectrum of antithrombotic and antiinflammatory activities. We hypothesized that NCX-4016 might inhibit in vivo lipopolysaccharide (LPS)-induced expression of tissue factor (TF). Methods and Results-Rats were administered 90 mg/kg NCX-4016 orally for 5 days. Placebo, 50 mg/kg ASA, and 80 mg/kg isosorbide-5-mononitrate (ISMN) were used in control groups. On day 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 40 publications
4
40
2
Order By: Relevance
“…1a) is the prototype of a new class of antiplatelet and anti-inflammatory drugs obtained by coupling a NO-releasing moiety to acetylsalicylic acid (Wallace et al, 1999(Wallace et al, , 2002Fiorucci et al, 2000Fiorucci et al, , 2002bFiorucci et al, , 2003Fiorucci and Del Soldato, 2003). NCX-4016 inhibits COX-1 and COX-2 activity (Wallace et al, 1999(Wallace et al, , 2002Fiorucci et al, 2002a;Fiorucci and Del Soldato, 2003) and triggers ATL formation in vivo (Fiorucci et al, 2003). Previous studies in rodents have shown that NCX-4016 is more effective than aspirin in preventing myocardial infarction and restenosis after carotid angioplasty (Wallace et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1a) is the prototype of a new class of antiplatelet and anti-inflammatory drugs obtained by coupling a NO-releasing moiety to acetylsalicylic acid (Wallace et al, 1999(Wallace et al, , 2002Fiorucci et al, 2000Fiorucci et al, , 2002bFiorucci et al, , 2003Fiorucci and Del Soldato, 2003). NCX-4016 inhibits COX-1 and COX-2 activity (Wallace et al, 1999(Wallace et al, , 2002Fiorucci et al, 2002a;Fiorucci and Del Soldato, 2003) and triggers ATL formation in vivo (Fiorucci et al, 2003). Previous studies in rodents have shown that NCX-4016 is more effective than aspirin in preventing myocardial infarction and restenosis after carotid angioplasty (Wallace et al, 2002).…”
mentioning
confidence: 99%
“…Previous studies in rodents have shown that NCX-4016 is more effective than aspirin in preventing myocardial infarction and restenosis after carotid angioplasty (Wallace et al, 2002). In contrast to aspirin, but similarly to NO donors, NCX-4016 modulates the expression of tissue factor on monocytes (Fiorucci et al, 2002a) as well as cytokine secretion from activated macrophages (Fiorucci et al, 2000), thereby suggesting that both the aspirin and the NO moiety contribute to its pharmacological activity.…”
mentioning
confidence: 99%
“…NCX-4016 is a NO-releasing derivative of aspirin (16)(17)(18)(19)(20)(21). Both the aspirin and the NO-releasing moieties of this compound contribute to its effectiveness (16).…”
mentioning
confidence: 99%
“…Both the aspirin and the NO-releasing moieties of this compound contribute to its effectiveness (16). Thus, not only does NCX-4016 inhibit COX-1 and COX-2 activity in vivo (16)(17)(18) and in vitro (19), it also increases platelet cyclic guanosyl monophate concentrations (17), inhibits platelet aggregation induced by adenosine diphosphate and thrombin (i.e., aspirinresistant aggregation) (16), and modulates tissue factor expression and activity in vivo and in vitro (19). Consistent with the fact that NO is a multifunctional regulatory molecule and mediates many components of gastrointestinal mucosal defence (20), NCX-4016 spares the gastrointestinal tract in healthy human volunteers (21) while retaining antiplatelet activity.…”
mentioning
confidence: 99%
“…NO is an extremely reactive molecule which can directly or indirectly interact with a variety of targets, including transcriptional regulators, enzymes and receptors (32)(33)). An anti-inflammatory effect of NO at micromolar concentrations has been suggested by studies demonstrating inhibition of Th-l-dependent cytokines (IL-l, IL-18 and IFN -), T lymphocyte proliferation, T-cell-mediated diseases (32)(33)(35)(36) and lipopolysaccharide-induced expression of tissue factor (37). However, in our experiments, a significant increase in extracellular nitrite, indicating a large NO formation at the dose used, was detected only after the administration ofHCT-1026.…”
Section: Body Weightmentioning
confidence: 99%